Association of Lipids With Ischemic and Hemorrhagic Stroke: A Prospective Cohort Study Among 267 500 Chinese. Issue 12 (December 2019) - Gu, Xiaoying; Li, Yunzhi; Chen, Shuohua; Yang, Xueli; Liu, Fangchao; Li, Ying; Li, Jianxin; Cao, Jie; Liu, Xiaoqing; Chen, Jichun; Shen, Chong; Yu, Ling; et al.
Abstract : Background and Purpose—: Previous results on the association between lipids and stroke were controversial. We investigated the association of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C ), high-density lipoprotein cholesterol (HDL-C), and triglyceride with stroke. Methods—: Six cohort studies in China with 267 500 participants were included. Cox proportional hazards regression models and restricted cubic spline analyses were used to estimate hazard ratios and 95% CIs and explore linear and nonlinear relationships of lipids and stroke, respectively. Results—: The median follow-up duration ranged from 6 to 19 years. During 2 295 881 person-years, 8072 people developed stroke. Multivariable adjusted hazard ratios (95% CIs) per 1 mmol/L increase in TC, LDL-C, triglyceride were 1.08 (1.05–1.11), 1.08 (1.04–1.11), 1.07 (1.05-1.09) for ischemic stroke, respectively. Compared with participants with TC 160-199.9 mg/dL, hazard ratios (95% CIs) were 1.43 (1.11–1.85) for hemorrhagic stroke in those with TC <120 mg/dL. Compared with participants with HDL-C 50 to 59.9 mg/dL, hazard ratios (95% CIs) were 1.23 (1.12–1.35), 1.13 (1.04–1.22) for ischemic stroke, and 1.28 (1.10–1.49), 1.17 (1.03–1.33) for hemorrhagic stroke in those with HDL-C <40 and 40 to 49.9 mg/dL, respectively. Restricted cubic spline analyses showed linear relationships of TC and LDL-C, and nonlinear relationships of HDL-C and triglyceride with ischemic stroke (all P <0.001). Hemorrhagic stroke showed linear relationships with TC and HDL-C ( P =0.029 and <0.001 respectively), but no relationship with LDL-C and triglyceride (all P >0.05). Conclusions—: TC, LDL-C, and triglyceride showed positive associations with ischemic stroke. The risk of hemorrhagic stroke was higher when TC was lower than 120 mg/dL. LDL-C and triglyceride showed no association with hemorrhagic stroke. The risks of ischemic and hemorrhagic stroke might be higher when HDL-C was lower than 50 mg/dL. Abstract : Supplemental Digital Content is available in the text.